TRANSLATION OF LINGUOCULTUREMES IN LITERARY WORKS: A COGNITIVE-PRAGMATIC APPROACH AND THE PROBLEM OF ADEQUACY - Madaliyeva , Ozoda (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The dynamics of modern translatological research necessitate a cognitive re-evaluation of preserving national-cultural characteristics within literary texts. The current investigation analyzes the multidimensional dynamics of pragmatic transformations occurring during the translation of linguoculturemes from the source to the target language. Empirical data demonstrate that units representing the cultural code of the original work must be decoded by the translator not only at the linguistic but also at the extralinguistic level. Within the scope of the research object, 185 linguocultural units extracted from Ernest Hemingway’s "The Old Man and the Sea" were subjected to comparative analysis. The dynamics of the obtained results quantitatively delineated the ratio of "foreignization" and "domestication" strategies. Analytical conclusions confirm that applying explication and cultural compensation methods in translating household and marine realia lacking equivalents in the target language increases receptional adequacy up to 78.4 percent. These findings establish critical strategic directions for creating adequate translation models of linguocultural units within Uzbek translation studies.